Training, Competetion & Health - Königstein K; 2; Niess AM; Carlsohn A; Treff G (Dynamic Media Sales Verlag, 2022)
Hydration management is challenging, but adequate hydration is of importance for health and performance in elite and recreational athletes. This brief, scoping review summarizes important aspects of hydration management in sports and offers practical guidance. We focus on the health risks of hypo- and hyperhydration and highlight preventive and therapeutic strategies. References may guide the interested reader towards more extensive literature on further aspects related to hydration and nutrient management during competition, training, and recovery.The physiological loss of fluid during prolonged exercise (i.e. marathon running, repeated training sessions within a day, multi-match sports event) occurs mainly through sweat, metabolic water and respiration. Substantial hypohydration (i.e., >2-4% of body mass) is likely to decrease performance and should be avoided. If athletes seek to prevent hypohydration by overdrinking, this can impose exercise associated hyponatremia and life-threatening cerebral edema. Overdrinking can generally be avoided by drinking to thirst, but individual rehydration strategies for training and competition may be advisable when barriers such as competition stress or poor availability are present. A variety of methods exists to assess hydration status in laboratory settings or in the field. Urine and blood markers combined with body mass changes currently offer the optimum of feasibility and validity.Key Words: Dehydration, Hypohydration, Rehydration, Hyperhydration, Plasma Osmolality, Urine Specific Gravity, Sweat, Sodium, Hydration Assessment, Exercise